2021
DOI: 10.3389/fpsyg.2021.719447
|View full text |Cite
|
Sign up to set email alerts
|

Verb-Mediated Prediction in Bilingual Toddlers

Abstract: Prediction is an important mechanism for efficient language processing. It has been shown that as a part of sentence processing, both children and adults predict nouns based on semantically constraining verbs. Language proficiency is said to modulate prediction: the higher proficiency, the better the predictive skill. Children growing up acquiring two languages are often more proficient in one of them, and as such, investigation of the predictive ability in young bilingual children can shed light on the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Several studies investigated individual variation in linguistic prediction skills and found associations with aspects of language experience/proficiency in adults for language production (Martin et al, 2018), receptive vocabulary (Rommers et al, 2015), literacy (Favier et al, 2021), and nativity (Reuter et al, 2021). Similar associations have been found in children between linguistic prediction abilities and input frequency (Garcia et al, 2021), language production (Brouwer, Sprenger, et al, 2017), receptive vocabulary (Borovsky et al, 2012), productive vocabulary (Mani & Huettig, 2012), literacy (Mani & Huettig, 2014), and language dominance for bilingual children (Theimann et al, 2021). Besides linguistic skills, prior work has also found associations between prediction abilities and cognitive skills such as working memory (WM) capacity in adults (Huettig & Janse, 2016;Ito et al, 2018).…”
mentioning
confidence: 72%
“…Several studies investigated individual variation in linguistic prediction skills and found associations with aspects of language experience/proficiency in adults for language production (Martin et al, 2018), receptive vocabulary (Rommers et al, 2015), literacy (Favier et al, 2021), and nativity (Reuter et al, 2021). Similar associations have been found in children between linguistic prediction abilities and input frequency (Garcia et al, 2021), language production (Brouwer, Sprenger, et al, 2017), receptive vocabulary (Borovsky et al, 2012), productive vocabulary (Mani & Huettig, 2012), literacy (Mani & Huettig, 2014), and language dominance for bilingual children (Theimann et al, 2021). Besides linguistic skills, prior work has also found associations between prediction abilities and cognitive skills such as working memory (WM) capacity in adults (Huettig & Janse, 2016;Ito et al, 2018).…”
mentioning
confidence: 72%